Modulation of the Inflammatory Response by Pre-emptive Administration of IMT504 Reduces Postoperative Pain in Rats and has Opioid-Sparing Effects - Rubione, Julia (2023)
Despite the available knowledge on underlying mechanisms and the development of several therapeutic strategies, optimal management of postoperative pain remains challenging. This preclinical study hypothesizes that, by promoting an anti-inflammatory scenario, pre-emptive administration of IMT504, a noncoding, non-CpG oligodeoxynucleotide with immune modulating properties, will reduce postincisional pain, also facilitating therapeutic opioid-sparing. Male adult Sprague-Dawley rats with unilateral hindpaw skin-muscle incision received pre-emptive (48 and 24 hours prior to surgery) or postoperative (6 hours after surgery) subcutaneous vehicle (saline) or IMT504. Various groups of rats were prepared for pain-like behavior analyses, including subgroups receiving morphine or naloxone, as well as for flow-cytometry or quantitative RT-PCR analyses of the spleen and hindpaws (for analysis of inflammatory phenotype). Compared to vehicle-treated rats, pre-emptive IMT504 significantly reduced mechanical allodynia by 6 hours after surgery, and accelerated recovery of basal responses from 72 hours after surgery and onwards. Cold allodynia was also reduced by IMT504. Postoperative administration of IMT504 resulted in similar positive effects on pain-like behavior. In IMT504-treated rats, 3 mg/kg morphine resulted in comparable blockade of mechanical allodynia as observed in vehicle-treated rats receiving 10 mg/kg morphine. IMT504 significantly increased hindpaw infiltration of mesenchymal stem cells, CD4+T and B cells, and caused upregulated or downregulated transcript expressions of interleukin-10 and interleukin-1β, respectively. Also, IMT504 treatment targeted the spleen, with upregulated or downregulated transcript expressions, 6 hours after incision, of interleukin-10 and interleukin-1β, respectively. Altogether, pre-emptive or postoperative IMT504 provides protection against postincisional pain, through participation of significant immunomodulatory actions, and exhibiting opioid-sparing effects. Perspective: This preclinical study introduces the noncoding non-CpG oligodeoxynucleotide IMT504 as a novel modulator of postoperative pain and underlying inflammatory events. The opioid-sparing effects observed for IMT504 appear as a key feature that could contribute, in the future, to reducing opioid-related adverse events in patients undergoing surgical intervention.